Trust in government in Sweden and Denmark during the COVID-19 epidemic. Issue 5 (19th September 2021) - Nielsen, Julie Hassing; Lindvall, Johannes
Abstract: Did the different public-health policies that Sweden and Denmark pursued in the beginning of the COVID-19 pandemic result in different levels of public trust in governments' and health authorities' ability to guide the two countries safely through the pandemic? How did the level of trust change as the pandemic unfolded? And were there any cross-country differences in the correlates of trust? Using three original representative surveys conducted in Sweden and Denmark between late March and late June, 2020, this article answers these questions. It finds that Danes consistently trusted their government and health authorities more than the Swedes did. While Swedish trust was politicized and shaped by ideology from the onset of the pandemic, this only later became the case in Denmark. The findings provide insights into popular evaluations of different public-health policies in two otherwise similar countries, with implications for future policy making. Supplemental data for this article can be accessed online at: https://doi.org/10.1080/01402382.2021.1909964 .